Basis for the Age-related Decline in Intestinal Mucosal Immunity - Douglas L. Schmucker; Robert L. Owen; Robert Outenreath; Karine Thoreux (Clinical and Developmental Immunology)
The elderly are characterized by mucosal immunosenescence and high rates of morbidity and mortality associated with infectious diseases of the intestinal tract. Little is known about how the differentiation of immunoglobulin A (IgA) plasma cells in Peyer's patches (PPs) and their subsequent homing to the small intestinal lamina propria (LP) is affected by aging. Quantitative immunohistochemical analyses demonstrated a 2-fold increase in the number of IgA+ cells in the PPs, coupled with significant declines in the numbers of IgA+ and antibody-positive cells in the intestinal LP of senescent rats compared to young adult animals. These data suggest that aging diminishes the emigration of IgA immunoblasts from these lymphoid aggregates, as well as their migration to the intestinal LP. Flow cytometry and lymphocyte adoptive transfer studies showed 3- to 4-fold age-related declines in the homing of antibody-containing cells and mesenteric lymph node lymphocytes to the small intestines of rhesus macaques and rats, respectively. The number of peripheral blood IgA immunoblasts expressing the homing molecule α4β7 declined 30% in senescent rats. This was accompanied by a >17% decrease in the areal density of LP blood vessels staining positive for the cell adhesion molecule MAdCAM-1. Cumulatively, declines in expression of these homing molecules constitute a substantial age-related diminution of IgA immunoblast homing potential. In vitro antibody secretion by LP plasma cells, i.e. antibody secreted per antibody-positive cell, remains unchanged as a function of donor age. Intestinal mucosal immunosenescence is a consequence of reduced homing of IgA plasma cells to the intestinal LP as a result of declines in homing molecule expression.